Understanding Hand Hygiene Behavior in a Public Hospital in Benin Using the Theoretical Domain Frameworks: The First Step for Designing Appropriate Interventions... - Yehouenou, Carine Laurence; Abedinzadeh, Aynaz; Houngnihin, Roch; Baxerres, Carine; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; Simon, Anne; Dalleur, Olivia (My University, 2022)
Abstract: Background: Hand Hygiene (HH) is widely recognized to be one of the most successful and cost-effective measures for reducing the incidence of healthcare-associated infections (HAIs). The hand hygiene behavior of hospital healthcare workers (HCWs) is not well-documented in Benin. Therefore, Theoretical Domains Framework (TDF) was used to identify the behavioral determinants that may impact HCWs’ hand-hygiene compliance in a public hospital. Methods: A qualitative design comprising face-to-face semi-structured interviews with nine HCWs. The interviews included questions on transmission of infections, hand-hygiene practices, problems with their implementation; and ways to improve hand hygiene compliance. Two pharmacists independently coded interviews into behavioral domains using the TDF and then subdivided them into several themes. Interview transcripts were analyzed following 3-steps approach: coding, generation of specific beliefs, and identification of relevant domains. Results: Almost all interviewees have cited the environmental context and resources (such as lack of water) as a barrier to HH practice. They also believed that role models had a significant impact on the good practices of others HCWs. Fortunately ,they were confident of their capabilities to perform appropriate HH behaviors. The majority (7/9) reported having the necessary knowledge and skills and believed they could carry out appropriate HH behavior. In all cases, the participants were motivated to carry out HH behavior, and it was recognized that HH remains the cornerstone to reduce health care associated infections. Conclusion: This study identified several behavioral constructs aligned with the TDF that can be targeted and help for the development of new hand-hygiene interventions. These may increase the likelihood of a successful intervention, thereby improving HH compliance and patient safety, especially in hospitals.
Keywords: hand hygiene compliance; healthcare workers; implementation science; theoretical domains framework; qualitative interviews; Beni